Effectiveness of the P5 Program in the Merdeka Curriculum to Increase the Creativity and Independence of Class V Elementary School Students - Abdul Muin; Siti Maisaroh; Wandri Ramadhan; Jamiu Temitope Sulaimon (Al Ibtida: Jurnal Pendidikan Guru MI)
This study aims to evaluate the effectiveness of the Strengthening Pancasila Student Profile (P5) Program within the Independent Curriculum at State Elementary School (SDN) 01 Tanjung Paku, SDN 06 Tanjung Paku, and SDN 10 Nan Balimo in Solok City, West Sumatra, during the 2023/2024 academic year. A mixed-methods approach was employed, integrating quantitative and qualitative methods. The quantitative approach involved surveys using Likert-scale questionnaires and standardized tests to assess the understanding and application of Pancasila values among fifth-grade students before and after participating in the P5 Program. The qualitative approach included in-depth interviews with fifth-grade teachers to gather their perspectives on program implementation and classroom observations to examine its integration into daily teaching and learning activities. The findings revealed a significant improvement in students' understanding and application of Pancasila values after participating in the P5 Program for one academic year. Quantitative data analysis indicated positive changes in students’ comprehension of Pancasila values. Meanwhile, qualitative analysis highlighted that while teachers faced challenges in implementing the program, they observed its positive impact on students’ creativity and independence. Therefore, it can be concluded that the P5 Program within the Independent Curriculum is effective in enhancing students’ understanding of Pancasila values and fostering their creativity and independence.